Factors Contributing to Work‐Life Balance Among Iranian Nurses Working in Clinical Settings: A Multicenter Cross‐Sectional Study - Reza Jotare; Akram Ghahramanian; Mansour Ghafourifard; Tonia C. Onyeka (Nursing Open)
ABSTRACT Aim To investigate work‐life balance (WLB) and its contributing factors among Iranian nurses in clinical settings. Design This multicenter cross‐sectional study collected data from 205 nurses using structured questionnaires. Methods Stratified random sampling was employed to select 205 nurses from three teaching hospitals in Tabriz, northwest Iran. Data were collected from March to June 2022. Participants completed a form detailing personal and work‐related information, along with Fisher's Work‐Life Balance Scale, which includes three subscales: Work Interference with Personal Life (WIPL), Personal Life Interference with Work (PLIW) and Work Personal Life Enhancement (WPLE). Results Nurses reported higher WIPL scores compared to PLIW scores. Those with master's degrees had significantly lower WIPL scores. Nurses contemplating early retirement were younger and showed higher WIPL and lower WPLE scores. Additionally, nurses' age was positively correlated with WPLE scores. Implications for Healthcare and Nursing Higher education levels may equip nurses with better skills to manage work demands, while those considering early retirement may experience increased pressures due to staffing shortages. The positive correlation between age and WPLE suggests that older nurses may have developed effective coping mechanisms or benefited from reduced work demands over time. Conclusion Iranian nurses experience significant work‐life imbalances, with work interfering more with personal life than vice versa. Factors such as education level, early retirement preferences and age influence WLB. However, this study's cross‐sectional nature limits causal inferences. Further longitudinal studies are needed to examine the dynamic relationship between work‐life factors and WLB in this population. No Patient or Public Contribution.